Increased Mortality in Underinsured Penetrating Trauma Patients. Issue 10 (October 2021) - Alaniz, Leonardo; Billimek, John; Figueroa, Cesar; Nahmias, Jeffry T.; Barrios, Cristobal
Introduction: It remains unclear whether an increased mortality risk in uninsured patients exists across Injury Severity Score (ISS) classifications. We hypothesized that penetrating trauma self-pay patients would have a similarly increased mortality risk across all ISS categories. Methods: The National Trauma Data Bank (2013-2015) was queried for patients presenting with penetrating firearm, explosive, or stab wound injuries. 115 651 patients were identified and a stratified multivariable logistic regression model was used. Results: In the >15 ISS group, self-pay patients had a lower median total hospital Length of Stay (LOS) (3 vs 8, P < .001), lower median Intensive Care Unit LOS (1 vs 3, P < .001), and lower median ventilator days (0 vs 1, P < .001). Self-pay patients had an increased risk for mortality compared to patients with private insurance in both the ≤15 ISS group (OR 2.68, P < .001) and >15 ISS group (OR 1.56, P < .001). Conclusion: Uninsured patients have an increased mortality risk in both low and high ISS groups. A higher mortality risk among uninsured patients in the high ISS group can be explained by decreased resource availability and lower ICU days and ventilator time. However, more studies are needed to determine why there is an even greater mortality risk among uninsured patients with mild ISS.